Pre-germination treatments with plant growth regulators and bioactivators attenuate salt stress in melon: effects on germination and seedling development (Acta Scientiarum. Agronomy, 2023)
The scarcity of surface water has led to the use of underground sources as an alternative for crop irrigation by farmers in semi-arid regions. However, these water sources generally have high salinity, which prevents agricultural production. The objective of this study was to determine the effects of pre-germination treatments with plant growth regulators and bioactivators on melon seeds to attenuate salt stress caused by irrigation water during germination and seedling development. Two trials were carried out separately with the hybrids, Goldex and Grand Prix. The design was completely randomized in a 4 Ã— 3 factorial scheme (four seed treatments and three dilutions of irrigation water). Seeds were treated with salicylic acid and gibberellic acid and the insecticide, thiamethoxam, in addition to the control. Local supply water, artesian well groundwater, and dilution of these waters at a 1:1 ratio were employed for irrigation. Fourteen days after sowing, morphological and physiological analyses were performed, and the material was collected for biochemical determination. The use of saline well water affected the initial development of melon seedlings of the Goldex and Grand Prix hybrids. Pre-germination treatment of Goldex hybrid seeds with gibberellic acid was inefficient at mitigating salt stress. However, the effects of irrigation water salinity on Grand Prix melon seeds pretreated with salicylic acid and thiamethoxam were attenuated.